Editorial Board - (PHR), Philippine Humanities Review (Philippine Humanities Review; Vol 25 No 1: Philippine Humanities Review (2023-2024): Rebyu ng Arte at Literatura ng Pilipinas, 2025)
Editorial Board PHR Staff